Distribution of leaf characteristics in relation to orientation within the canopy of woody species - Escudero, Alfonso; Fernández, José; Cordero, Angel; Mediavilla, Sonia (Acta Oecologica, 2013)
Over the last few decades considerable effort has been devoted to research of leaf adaptations to environmental conditions. Many studies have reported strong differences in leaf mass per unit area (LMA) within a single tree depending on the photosynthetic photon flux density (PPFD) incident on different locations in the crown. There are fewer studies, however, of the effects of differences in the timing of light incidence during the day on different crown orientations. Leaves from isolated trees of Quercus suber and Quercus ilex in a cold Mediterranean climate were sampled to analyze differences in LMA and other leaf traits among different crown orientations. Gas-exchange rates, leaf water potentials, leaf temperatures and PPFD incident on leaf surfaces in different crown orientations were also measured throughout one entire summer day for each species. Mean daily PPFD values were similar for the leaves from the eastern and western sides of the canopy. On the western side, PPFD reached maximum values during the afternoon. Maximum leaf temperatures were approximately 10–20% higher on the west side, whereas minimum leaf water potentials were between 10 and 24% higher on the east side. Maximum transpiration rates were approximately 22% greater on the west, because of the greater leaf-to-air vapor pressure deficits (LAVPD). Mean individual leaf area was around 10% larger on the east than on the west side of the trees. In contrast, there were no significant differences in LMA between east and west sides of the crown. Contrary to our expectations, more severe water stress on the west side did not result in increases in LMA, although it was associated with lower individual leaf area. We conclude that increases in LMA measured by other authors along gradients of water stress would be due to differences in light intensity between dry and humid sites.
Keywords: Canopy orientation; leaf morphology; Leaf temperature; Quercus; water potential

Environmental induced variations in leaf dark respiration and net photosynthesis of Quercus ilex L. - Gratani, L; Varone, L; Bonito, A (Photosynthetica, 2007)
The relationships between dark respiration rate (RD) and net photosynthetic rate (PN) in Quercus ilex L. shrubs growing at the Botanical Garden in Rome were analysed. Correlation analysis of the data sets collected in the year 2006 confirmed the dependence among the considered leaf traits, in particular, RD was significantly (p<0.05) correlated with PN (r = 0.40). RD and PN increased from March to May [1.40±0.10 and 10.1±1.8 μmol(CO2) m –2 s –1 mean values of the period, respectively], when air temperature was in the range 14.8–25.2 °C, underlining the highest metabolic activity in the period of the maximum vegetative activity that favoured biomass accumulation. On the contrary, the highest RD [1.60±0.02 μmol(CO2) m –2 s –1 ], associated to the lowest PN rates (44 % of the maximum) and carbon use efficiency (CUE) in July underlined the mobilization of stored material during drought stress by a higher air temperature (32.7 °C).
Keywords: carbon use efficiency; Leaf temperature; seasonal course

Leaf temperature effects on gas exchange in Quercus ilex L. growing under field conditions - Gratani, Loretta (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2000)
ABSTRACT Gas exchange temperature dependence in Quercus ilex shrubs growing in the Mediterranean maquis was analysed. The gas exchange trend was monitored during the year: photosynthetic activity (A net) reached the highest average rates in early spring and autumn (12.5 µmol m-2s-1 was the absolute maximum A net measured) and the lowest rates were monitored in the middle of June. There was a good correlation (r = 0.72) between A net and g s (A net = 4.1246 ln g s + 4316; P < 0.01), indicating that stomatal control of CO2 diffusion plays an important role in controlling photosynthetic activity. Leaf temperature allowing the highest photosynthetic and stomatal conductance rates of Quercus ilex were in the range 17.5 ? 29°C. A net and gs dropped below half its maximum value when leaf temperatures were below 11.5°C and above 35.7°C. Transpiration rates (E) were strongly related to leaf temperature; E increased as leaf temperature increased and the highest E rates were monitored in June, despite a 46% decrease in g s. Leaf water loss from transpiration, during the drought period, could result in leaf water stress which would exacerbate heat effects on photosynthesis. During summer, the increase in leaf temperatures decreased g s which in turn decreased A net. Consequently, stomatal control in Quercus ilex may be considered as an adaptive strategy during drought.
doi: 10.1080/11263500012331350295
Keywords: Leaf temperature; photosynthetic activity; Quercus ilex; Stomatal conductance